Electromagnetic fields in biological systems - Lin, James C. (Boca Raton : Taylor & Francis, 2011)
"Focusing on exposure, induced fields, and absorbed energy, this volume covers the interaction of electromagnetic fields and waves with biological systems, spanning static fields to terahertz waves. Presenting a broad range of topics, the book highlights relevant properties of biological materials and computational techniques and/or experimental methods. Topics discussed include medical devices and systems exposure and dosimetry and mobile communication fields in biological systems. Extensive references are included in each chapter to enhance additional study"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electromagnetism -- Physiological effect; Electromagnetic Fields -- adverse effects; Radiation, Nonionizing